2020
DOI: 10.3390/catal11010013
|View full text |Cite
|
Sign up to set email alerts
|

Ru/Ce/Ni Metal Foams as Structured Catalysts for the Methanation of CO2

Abstract: The development of highly conductive structured catalysts with enhanced mass- and heat-transfer features is required for the intensification of the strongly exothermic catalytic hydrogenation of CO2 in which large temperature gradients should be avoided to prevent catalyst deactivation and to control selectivity. Therefore, in this work we set out to investigate the preparation of novel structured catalysts obtained from a commercial open cell Ni foam with high pore density (75 ppi) onto which a CeO2 layer was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 48 publications
1
16
0
Order By: Relevance
“…The apparent activation energies are calculated to be approximately 84 kJ mol −1 for Ru3Ce97-Foam, 90 kJ mol −1 for Ni1Ce3-Foam, and 102 kJ mol −1 for both Ni1Ce3-Pellet and Ni3Ce1-Foam. These values of the activation energies are similar to those previously reported in the literature, e.g., 86.7 kJ mol −1 for 5 wt % Ru/CeO 2 catalyst 60 or 85.8 kJ mol −1 for Ru/Ni (direct electrodeposition on Ni foam) and 87.5 kJ mol −1 for Ru-impregnated on CeO 2 -coated Ni foam, 13 and in a range of 95−107 kJ mol −1 for Ni/CeO 2 catalysts. 61 Note that the apparent activation energy values depend on both the type of catalysts and the operating conditions (e.g., reactant composition, reduction temperature, and treatment conditions).…”
Section: Methodssupporting
confidence: 89%
See 1 more Smart Citation
“…The apparent activation energies are calculated to be approximately 84 kJ mol −1 for Ru3Ce97-Foam, 90 kJ mol −1 for Ni1Ce3-Foam, and 102 kJ mol −1 for both Ni1Ce3-Pellet and Ni3Ce1-Foam. These values of the activation energies are similar to those previously reported in the literature, e.g., 86.7 kJ mol −1 for 5 wt % Ru/CeO 2 catalyst 60 or 85.8 kJ mol −1 for Ru/Ni (direct electrodeposition on Ni foam) and 87.5 kJ mol −1 for Ru-impregnated on CeO 2 -coated Ni foam, 13 and in a range of 95−107 kJ mol −1 for Ni/CeO 2 catalysts. 61 Note that the apparent activation energy values depend on both the type of catalysts and the operating conditions (e.g., reactant composition, reduction temperature, and treatment conditions).…”
Section: Methodssupporting
confidence: 89%
“…40 An alternative is the impregnation of the noble metal, e.g., Ru, on the electrodeposited CeO 2 . 13 This work aims to prepare in a single-step Ru−CeO 2 and Ni−CeO 2 catalytic coatings on NiCrAl open-cell foams with small cell size (450 μm) to achieve both methanation activity at low temperature and enhanced heat transfer. The precipitation of CeO 2 containing Ni and Ru is performed for the first time by electrodeposition, more precisely, by the electro-base generation method.…”
Section: Introductionmentioning
confidence: 99%
“…447,448 The use of highly conductive Ru/Ce x /Ni foams has been investigated for the methanation reaction, demonstrating promise for the management of highly exothermic catalytic reactions. 449 Depending on the materials used for the structure and/or for the catalysts, different techniques exist and should be approached to identify the best one, with possible clogging and material coating feasibility that must be taken into account. 450 Fluidized bed reactors are another technology already used in some industrial processes, due to the almost perfect heat management, with small or even negligible temperature gradients, thanks to the fluidization of the bed.…”
Section: Reactor Technologiesmentioning
confidence: 99%
“…Therefore, refractory oxides with high thermal stability, in which the active metals can be amply dispersed, are typically required. 22 A recent statistical analysis of literature data reported by Yang et al 23 revealed that the reaction conditions (total pressure and reaction temperature) are decisive parameters affecting the rates of overall CO 2 conversion and formation of C 2+-hydrocarbons. Other key factors that influence the selectivity to C 2+-hydrocarbons and the ratio of olefins/ paraffins were: the catalyst design, its pretreatment time, and the selection of iron precursors.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, an increase toward C 5+ yield and lower C 1 production has been observed operating at lower temperatures and high hydrogen pressures. It is also possible to produce methane by the Sabatier reaction, better known as the methanation (M) reaction (eq ), which is slightly more exothermic than the FTS reaction. The exothermicity of both reactions (FT and M) could lead to hotspots in the reaction systems, causing deactivation and sintering. Therefore, refractory oxides with high thermal stability, in which the active metals can be amply dispersed, are typically required …”
Section: Introductionmentioning
confidence: 99%